Modelling and control of a Magnetic Levitation System - Motakabber, S. M. A.; Alam, A. H. M. Zahirul; Kamal, Khairul Izham (AlamBiblio Publishers, 2024)
Magnetic Levitation Systems (MLS), or Maglev for short, utilise magnetic fields to levitate objects. They find applications in various scientific fields, particularly transportation, materials science, and biomedical engineering. Due to the diverse applications, different modelling and control approaches are necessary. The operation of each Maglev system depends on specific physical parameters. These key variables include the weight of the object being levitated, the current supplied to the system, the internal resistance and inductance of the electromagnet, and the distance between the object and the electromagnet. This research aims to understand the working principles of MLS. We will design and simulate a model based on real MLS hardware using MATLAB & Simulink. Additionally, we will create a functional Maglev prototype and program its control system using Arduino IDE and an Arduino microcontroller. MATLAB & Simulink offer a powerful tool for creating behavioral models for MLS. This model will then be integrated with Arduino programming to control the Maglev prototype.